EXPERIENCE OF USING BEDAQUILINE IN THE TREATMENT OF PULMONARY TUBERCULOSIS PATIENTS WITH MULTIPLE ANDEXTENSIVE DRUG RESISTANCE - N. M. Konovаlovа; V. S. Odinets; T. I. Vаsilenko; T. A. Zаdremаylovа (Туберкулез и болезни лёгких, 2018)
The article presents the evaluation of safety and efficiency of chemotherapy regimens including the new anti-tuberculosis agent of bedaquiline in 21 pulmonary tuberculosis patients with multiple and extensive drug resistance who were treated in Stavropol Regional Clinical TB Dispensary from 2014 to 2017. It was found out that regimens with bedaquiline were satisfactory tolerated, and the attempt to identify the agent causing adverse events within a multi-component chemotherapy regimen failed. The majority of adverse events were reversible, but they required temporary cancellation of chemotherapy in 5 patients with the consequent continuation of treatment with this regimen after adverse events were managed. The evaluation of treatment efficiency with 6-month treatment with bedaquiline showed sputum conversion in 94.4% of cases and healing of cavities in 72.2%.